Quality Analysis of E-KTP Services at the Department of Population and Civil Registration of Semarang Regency (Universitas Negeri Semarang, 2022)
This study aimed to analyze the quality of e-KTP services at the Department of Population and Civil Registration (Dukcapil) of Semarang Regency. This research used descriptive qualitative research. Informants in this study were 14 informants consisting of 4 apparatus and 10 service users. Data collection techniques used observation, interviews and documentation. Data analysis used data collection, data reduction, data presentation and drawing conclusions. The results of the study indicated that in the Tangible dimension, there were two indicators that were not optimal, namely the ease of service processes and the use of service tools. In the Reliability dimension, there was one indicator that was not optimal, namely having clear service standards. In the Assurance dimension (Guarantee), there was one indicator that was not optimal, namely providing guarantees on time. Meanwhile, the Responsiveness and Empathy dimensions had been said to be optimal in the application of each indicator. The conclusion from this study, the implementation of e-KTP services at Dukcapil Semarang Regency had not been fully optimal, as evidenced by the existence of indicators that had not been implemented properly. The advice given is to be able to provide facilities in the form of providing service officers who stand by near the entrance to the service room so that it is easy to reach, always improve the quality of service aids, especially for tools that often have problems, adjust to the circular letter of Presidential Regulation number 96 of 2018, coordinate further related to the distribution of e-KTP with the POS office in order to minimize delays.